REVIEW OF CLINICAL TRIALS DURING THE COVID-19 PANDEMIC - M.Nedelchev; Y.Nedelcheva (Trakia Journal of Sciences)
Objective: The systematic data on clinical trials during the COVID-19 pandemic are scarce. We aimed to review the dynamics of clinical trials in the new reality. Materials and methods: We collected data for all 112 clinical trials completed or prematurely ended in 2019-2021. The main data sources are the Register of Authorized Clinical Trials, the Bulgarian Drug Agency, and the European Union Clinical Trials Register of the European Union Drug Regulating Authorities Clinical Trials Databases. Results: General information of clinical trials is aligned with international trends, while the population of trial subjects is in line with the demographic situation in Bulgaria. The adaptability of trial sites to conduct multi-regional trials is the newest factor for clinical trials dynamics. Conclusions: The size of country’s population is not a factor in the dynamics of clinical trials. A therapeutic area of clinical trials in line with local trends and the adaptability of trial sites to the international trends of most common diseases are attractive factor for conducting clinical trials in Bulgaria.